The Improvement of Student Learning Outcomes in Civics Education (PKn) through the Active Learning Approach in Class V at UPT SDN 262 Pinrang - Nur Qhadijah; Dian Firdiani; Rahmat Rahmat (Edumaspul: Jurnal Pendidikan, 2024)
This classroom action research aims to improve student learning outcomes in Pancasila and Civic Education through the implementation of the Active Student Learning Approach in grade V at UPT SDN 262 Pinrang. The research method uses a classroom action research design implemented in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The research subjects involved 32 fifth-grade students with data collection techniques through learning outcome tests, student activity observation sheets, and documentation. Data analysis was conducted descriptively both quantitatively and qualitatively to measure the improvement in learning outcomes and student activities during the learning process. The results showed a significant increase in student learning outcomes from the pre-cycle with an average score of 65.78 increasing to 73.44 in cycle I and reaching 82.19 in cycle II. The percentage of classical completeness also increased from 46.88% in the pre-cycle to 71.88% in cycle I and reached 87.50% in cycle II. Student learning activities showed improvement from the moderately active category to very active. The research conclusion indicates that the implementation of the Active Student Learning Approach is effective in improving learning outcomes and student activities in Civic Education subject in grade V at UPT SDN 262 Pinrang.